A case series of congenital nevus and their various manifestations - Bibekananda Mukherjee; Barnali Das; Joydeep Das; Apurba Ghosh (Asian Journal of Medical Sciences, 2023)
A nevus is characterized by collection of partially differentiated or well-differentiated cells normally found in the skin. Some nevi are associated with disorders such as autism, epilepsy, ophthalmogical disorders, intracranial abnormalities, and others. In this case series, we aim to analyze six cases with congenital nevus, matched our findings with case reports published and reviewed the literature, to come to a conclusion that would help the clinician to do focused clinical examination and investigations when they come across such nevi. Furthermore, as these sort of skin lesions cause psychological morbidity to both parents and patients, proper counseling is required along with dermatological therapy and treatment of comorbid conditions. As well as regular follow-up with monitoring of the lesions. The following are the cases: Case-1, is a case of congenital melanocytic nevi who presented with delayed milestone, epilepsy and neuroimaging revealed intracranial melanosis. Case-2 nevus of Ota on face with scleral nevus and glaucoma in the left eye. In Case-3: Nevus achromicus was present over the abdomen and scalp in a child who presented with status epilepticus and there was focal cortical dysplasia of left frontal cortex on imaging. Nevus sebaceous was present in case-4 who had seizure disorder but neuroimaging was normal. Case-5 child had nevus spilus over left frontal area with melanocytic satellite nevi who presented with febrile convulsion but normal neuroimaging. The sixth case is a 5-year-old male child with linear nevus without any other association.